Erythropoietin: function and therapeutic potential - A. P. Lykov (Сибирский научный медицинский журнал, 2023)
Erythropoietin (EPO) exerts its eﬀect on erythroid lineage cells through interaction with the EPO receptor (EPOR), the so-called canonical pathway, and through a complex consisting of EPOR and a common cytokine receptor beta subunit (CD131) – a non-canonical pathway for non-hematopoietic cells of the human and animal body. EPO realizes its eﬀects through the launch of a signaling cascade, which begins with the phosphorylation of Janus kinase 2 (JAK2) and then with the involvement of phosphatidylinositol-3 kinase B (PI3K) or Ras-mitogen-activated protein kinase (MAPK) or signal transducers and transcription activators (STAT). EPO exhibits a direct cytoprotective eﬀect through increased CD131 expression and subsequent development of anti-apoptotic and anti-inﬂammatory eﬀects in target cells. In addition to its use in the treatment of anemia, EPO is increasingly being used in correction of inﬂammatory and degenerative processes, both in experimental and clinical studies. EPO promotes the engraftment of stem cells, diﬀerentiation of mesenchymal stem cells in the connective tissue direction, suppresses the inﬂammatory response and apoptosis of cells in the lesion. The article includes literature data concerning EPO and its clinical use in inﬂammatory and degenerative processes, based on data from eLibrary and the National Center for Biotechnological Information (NCBI) for the period 1998–2022.